Life expectancy tables for dogs and cats derived from clinical data - Montoya, Mathieu; Morrison, Jo Ann; Arrignon, Florent; Spofford, Nate; Charles, Hélène; Hours, Marie-Anne; Biourge, Vincent (Frontiers in Veterinary Science, 2023)
There are few recent and methodologically robust life expectancy (LE) tables for dogs or cats. This study aimed to generate LE tables for these species with clinical records from >1000 Banfield Pet hospitals in the USA. Using Sullivan’s method, LE tables were generated across survey years 2013–2019, by survey year, and for subpopulations defined by sex, adult body size group (purebred dogs only: toy, small, medium, large and giant), and median body condition score (BCS) over life. The deceased population for each survey year comprised animals with a recorded date of death in that year; survivors had no death date in that year and were confirmed living by a veterinary visit in a subsequent year. The dataset totaled 13,292,929 unique dogs and 2,390,078 unique cats. LE at birth (LEbirth) was 12.69 years (95% CI: 12.68–12.70) for all dogs, 12.71 years (12.67–12.76) for mixed-breed dogs, 11.18 years (11.16–11.20) for cats, and 11.12 (11.09–11.14) for mixed-breed cats. LEbirth increased with decreasing dog size group and increasing survey year 2013 to 2018 for all dog size groups and cats. Female dogs and cats had significantly higher LEbirth than males (12.76 years (12.75–12.77) versus 12.63 years (12.62––12.64), and 11.68 years (11.65–11.71) versus 10.72 years (10.68–10.75), respectively). Obese dogs (BCS 5/5) had a significantly lower LEbirth (11.71 years (11.66–11.77)) than overweight dogs (BCS 4/5) (13.14 years (13.12–13.16)) and dogs with ideal BCS 3/5 (13.18 years (13.16–13.19)). The LEbirth of cats with BCS 4/5 (13.67 years (13.62–13.71)) was significantly higher than cats with BCS 5/5 (12.56 years (12.45–12.66)) or BCS 3/5 (12.18 years (12.14–12.21)). These LE tables provide valuable information for veterinarians and pet owners, a foundation for research hypotheses, and are a stepping-stone to disease-associated LE tables.